A N-doped carbon nanocages@silicon nanoparticles microcapsules for high-performance Li-storage. (December 2022) - Yu, Hao; Gu, Fengling; Chen, Shouhui; Du, Yan; Wang, Li; Song, Yonghai
Abstract: Silicon (Si) is an ideal anode materials of lithium-ion batteries (LIBs) due to its ultrahigh theoretical capacity. However, its commercialization is severely hampered because the intrinsic poor electrical conductivity and huge volume expansion during lithiation/delithiation process lead to rapid capacity decay. Designing Si/carbon composite is a feasible way for enhancing performance of Si. Here, a porous N-doped carbon nanocages@Si nanoparticles (NC@Si-20) microcapsules was prepared by encapsulating Si nanoparticles (SiNPs) into zeolitic imidazolate frameworks-90 (ZIF-90), coating covalent-organic frameworks (COFs) with well-ordered pores around ZIF-90@SiNPs, etching ZIF-90, and calcining COFs@SiNPs under N2 in turn. The porous N-doped carbon nanocages derived from COFs formed three-dimensional protective shells around SiNPs, which not only improved the electrical conductivity of microcapsules but also provided more buffer space for volume expansions of SiNPs to slow down the attenuation of capacity. When applying for the anode of LIBs, the obtained NC@Si-20 microcapsules showed high capacity of 1015 mAh g −1 at 100 mA g −1 after 100 cycles and good cycling stability. The approximate theoretical capacity contribution of Si can be up to 2363 mAh g −1 . Combining with the benefits of both carbon nanocages derived from COFs (stability and recyclability) and Si (high capacity), this work developed a promising material for LIBs. Graphical abstract: Image 1 Highlights: A N-doped carbon nanocages@silicon nanoparticle (NC@Si-20) microcapsule was synthesized. The NC@Si-20 microcapsule provides large spaces for volume expansion of SiNPs and slows down capacity decay. The porous N-doped carbon nanocage facilitates Li + transfer to contact with SiNPs. NC@Si-20 shows high capacity of 1015 mAh g −1 at 100 mA g −1 after 100 cycles and good cycling stability. The Si in NC@Si-20 microcapsule shows a superior theoretical capacity contribution of 2362 mAh g −1 .